(untitled) (Research, Society and Development, 2021)
Objective: the aim of our study was to assess the effect of a physical activity that uses active video games in body composition, physical fitness, cardiovascular and biochemical parameters with sedentary adolescents. Methods: a non-controlled clinical trial design with a convenience sample of adolescents, separately, from ages ten to 17, of both genders. The intervention protocol consisted of physical activity with active video games (AVG), lasting two months, in 24 sessions, evolving into three levels (basic, intermediate and advanced) according to the maximum heart rate of the individuals. The adolescents’ body composition, physical fitness, cardiovascular and biochemical parameters were assessed. Data analysis was performed with a 95% confidence interval. Results: among the 14 adolescents that completed the physical training, we observed a improvement of muscle resistance (Δ= 8.26; p= 0.02) and decrease in post-exercise heart rate and systolic blood pressure (p< 0.01). However, were found a non-significant decrease in body fat percentage (Δ= -3.83; p= 0.24) and strength (Δ= 4.26; p= 0.57). A high level of satisfaction with the proposed activity was identified. Conclusion: a physical activity program based on AVG can reduce cardiovascular risk factors and improve muscle resistance in sedentary adolescents.